PENGARUH AKTIVITAS PERTAMBANGAN BATUBARA TERHADAP KONDISI LINGKUNGAN DAN SOSIAL DI KALIMANTAN TIMUR - Yustia Wiranti; Uswatunhasanah, Retno Dewi; Hotimah, Oot; Adilah, Nazhirah (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2025)
Coal mining activities in East Kalimantan have had a significant impact on the environmental and social conditions of the local community. Although this industry contributes significantly to the regional economy, various problems such as land degradation, water pollution, and socio-economic changes cannot be ignored. This study aims to analyze the impact of coal mining on the environment and social life of the community in East Kalimantan. The research methods used are literature review and secondary data analysis from various reliable sources. The results show that coal mining activities cause deforestation, decreased water quality due to mining waste, and changes in the economic structure and livelihoods of the community. To overcome these negative impacts, stricter policies on environmental management are needed, as well as community empowerment so that they can adapt to the social changes that occur. This study is expected to provide insights for policymakers and academics in developing more sustainable mining impact mitigation strategies.